2010
DOI: 10.1002/jcp.22023
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen‐activated protein kinase‐activated protein kinase 2 (MK2) in skeletal muscle atrophy and hypertrophy

Abstract: Skeletal muscle is a highly plastic tissue. Overall muscle growth (hypertrophy) or muscle wasting (atrophy) results from alterations in intracellular signaling pathways with important regulatory steps occurring in the nucleus as well as in the cytoplasm. Previous studies have identified components of the Akt/mTor pathway as well as the p38 MAPK pathway as important for skeletal muscle hypertrophy and/or atrophy. The present study tests the hypothesis that MK2, a substrate of p38 which following phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 60 publications
(72 reference statements)
5
12
0
Order By: Relevance
“…The present study confirms previous observations [48] of increased MK2 T205 phosphorylation in denervated skeletal muscle and a differential response of MK2 T317 phosphorylation to denervation in hemidiaphragm (hypertrophic, increased T317 phosphorylation) and anterior tibial muscle (atrophic, decreased T317 phosphorylation). The present study also shows increased MK2 T205 phosphorylation and decreased T317 phosphorylation in denervated atrophic pooled gastrocnemius and soleus muscles.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study confirms previous observations [48] of increased MK2 T205 phosphorylation in denervated skeletal muscle and a differential response of MK2 T317 phosphorylation to denervation in hemidiaphragm (hypertrophic, increased T317 phosphorylation) and anterior tibial muscle (atrophic, decreased T317 phosphorylation). The present study also shows increased MK2 T205 phosphorylation and decreased T317 phosphorylation in denervated atrophic pooled gastrocnemius and soleus muscles.…”
Section: Discussionsupporting
confidence: 93%
“…Denervation of skeletal muscles generally causes atrophy of the muscles but the hemidiaphragm becomes transiently hypertrophic following denervation [45-48]. We have previously shown that the MK2 phosphorylation on T317 correlates with muscle weight in denervated atrophic anterior tibial muscle, denervated hypertrophic hemidiaphragm muscle and innervated control muscles [48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…p38 MAPK is responding to both anabolic (e.g., muscle cell stretch, functional overload) and catabolic stimuli (e.g., tumor necrosis factor α) (21,27,44). In the present study, phosphorylated p38 MAPK was elevated after the resistance loading in line with previous reports in humans (4,19,39,41).…”
Section: Discussionsupporting
confidence: 82%
“…From a simple point of view, skeletal muscle growth or hypertrophy and muscle wasting or atrophy result both from complex changes in intracellular signaling pathways in the nucleus and cytoplasm, involving the components of the Akt/mTor and the p38 MAPK pathways. MK2 (mitogen-activated protein kinase-activated protein kinase 2) participates in the regulation of muscle mass and determines the subcellular localization of p38 in muscle fibers, being phosphorylated and both exported from the nucleus in a complex with p38, involved with skeletal muscle growth [22].…”
Section: Genetic and Molecular Mechanisms Involved With Muscular Atromentioning
confidence: 99%